2021
DOI: 10.1111/nicc.12676
|View full text |Cite
|
Sign up to set email alerts
|

Identifying teamwork‐related needs of the medical emergency team: Nurses' perspectives

Abstract: Background: The role of medical emergency team (MET) in managing deteriorating patients and enhancing patient safety is greatly affected by teamwork.Aims: To identify teamwork-related needs of the MET from MET nurses' perspectives. To assess the associations between MET nurses' perceptions of teamwork and their work experience and education.Study design: A quantitative, descriptive correlational design.Methods: Registered intensive care unit (ICU) nurses (n = 50) who were members of the MET in an acute tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Of the 28 included studies, 25 were quantitative, 4,13–36 two were qualitative, 37,38 and one was a mixed‐methods study 39 . Studies with a quantitative design included nine cohort, six case–control, four secondary analyses, three descriptive, two feasibility, and one cross‐sectional study.…”
Section: Results/findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 28 included studies, 25 were quantitative, 4,13–36 two were qualitative, 37,38 and one was a mixed‐methods study 39 . Studies with a quantitative design included nine cohort, six case–control, four secondary analyses, three descriptive, two feasibility, and one cross‐sectional study.…”
Section: Results/findingsmentioning
confidence: 99%
“…Studies relevant to the night‐time MET/RRT response showed that this category was either referred to as a MET or an RRT 13–26 . All these studies had been designed using quantitative methodologies that only included observational studies.…”
Section: Results/findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other papers in this issue employ a range of methodologies to address various clinically relevant topics, namely delirium in critically ill adults 10 and children 11 ; nurse–nurse 12 and nurse‐doctor collaboration 13 and teamwork 14 ; sleep quality 15,16 ; sedation and pressure injuries 17 and ABCDE bundle implementation 18 …”
mentioning
confidence: 99%